SPLDV QUESTION SOLUTION PROFILE OF MTs ALKHAIRAT TOMINI STUDENTS BASED ON STUDENT LEARNING STYLE - Raiyan Raiyan; Sukayasa Sukayasa; Anggraini Anggraini; I Nyoman Murdiana (JME (Journal of Mathematics Education), 2023)
This research aims to obtain a description of the problem-solving profile of two-variable linear equation systems of MTs Al-Khairat Tomini students based on the student's learning styles. This type of research is qualitative. The subjects of this research were three students in class VIII B MTs Al-Khairat tomini, each consisting of one student with visual, auditory, and kinesthetic learning styles. Data on student problem-solving was obtained from written tests and interviews. Thisresearch shows that the subject (IN) carries out the problem-solving plan by the solution plan questions, and the subject did not recheck the problem-solving because he did not understand how to do it. The subject (MA) carries out the problem-solving plan by the problem solving plan, and the subject can check and solve questions by checking the written answers again.